Assessment of Lead and Arsenic in Soils From Paddy Fields - Fauzul, Hafsa Faizal (2017)
There are major environmental and health concerns associated with heavy metal contamination in the soil as they are regarded as poisonous trace elements in the environment. The current study examines the concentration of lead (Pb) and arsenic (As) in the paddy field soils which were collected from Bahau, Negeri Sembilan and Sekinchan, Selangor. The total metal concentrations were determined by treating the soil with aqua-regia method as well as sequential extraction technique (SET) to distinguish the origin of heavy metal. The metals EFLE, acid reducible, oxidizable and resistant fractions concentration were determined using inductively coupled plasma mass spectrometry (ICP-MS). Overall both sites were extremely contaminated by both Pb and As exceeded the permissible limit with the highest value of 5900.00 μg/g dw and 6038.38 μg/g dw when compared with standards of China and Germany. The Pb was found highest at the acid reducible fraction indicating that Fe-Mn concentration is the contributing factor for the fixation of Pb to the soil surface and making them not bioavailable to plants, whereby As was always found in low level compared to Pb in all fractions. Factors such as soil pH, texture, target elements and organic matter content affect the metals bioavailability and their existence in soil. Hence, the metals bioavailability was studied by carrying out the pH analysis and organic matter content of the soil. Soils of Sekinchan showed an alkaline pH 7.05 and Bahau acidic pH of 5.02. Organic matter was higher at Sekinchan fields 124% compared to Bahau which was 88%.